Service system innovation and firm competitiveness in an emerging market: The role of corporate governance system - Akpan Ekom Etim; Anthony Aniagbaoso Igwe; Mamdouh Abdulaziz Saleh Al-Faryan; Ben Etim Udoh (Cogent Business & Management, 2023)
The study empirically examined the effect of service system innovation on firm competitiveness in Nigeria, an emerging market, focusing on the country's telecommunication sector. Additionally, the moderating effect of the corporate governance system on service system innovation-firm competitiveness nexus was observed. Data were collected using a survey instrument from 230 respondents. The study followed a cross-sectional research design while the study hypotheses were tested using the partial least square-structural equation model (PLS-SEM). Analyses revealed that service system innovation as represented by idea development, service development, and commercialization enhance firm competitiveness. Implying that idea development, service development, and commercialization are essential for higher levels of firm competitiveness. In addition, corporate governance system was found to boost the relationship between service system innovation and firm competitiveness. The study offers new understanding into the role of service system innovation in competitiveness of the telecommunication firms especially in developing economies such as Nigeria. The study also shows that the corporate governance system contributes significantly to the success of telecommunication firms. Further, the study provides evidence on the characteristics of service system innovation, corporate governance system, and firm competitiveness within the telecommunication industry. In addition, the study developed and validated an instrument for measuring service system innovation, firm competitiveness, and corporate governance system within a developing economy which may be adopted by future studies when examining these variables. Furthermore, the study confirms the usefulness of dynamic capabilities theory in understanding service system innovation, firm competitiveness, and corporate governance.
Keywords: O31; G34; L96; 650; and corporate governance system; commercialization; idea development; organizational competitiveness; service development; Service system innovation